Konsumsi Media Sosial Bagi Kalangan Pelajar: Studi Pada Hyperrealitas Tik Tok - Mukhammad Handy dwi Wijaya; Musta’in Mashud (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
The phenomenon of Tik Tok which has become an acute epidemic among students does not only occur in big cities. In almost all parts of the country, this phenomenon has become a trend. No exception in small cities like Blitar, East Java. Though not realized, they have been trapped in a simulation world full of unreality (artificial). That is something that looks more than what actually happened. Tik Tok appears to facilitate the existence of a person beyond its essence. The reality that is displayed through Tik Tok is actually a hyper and pseudo reality. Literally, hypereality can be interpreted as a condition that transcends reality. Hyperreality is often found in cyberspace when the distinction between reality and fiction is blurred. Baudrillard states that current consumption has become a sign of consumption. The act of consumption of goods and services is no longer based on their use but rather prioritizes the signs and symbols attached to the goods and services themselves so that people as consumers are never satisfied and will lead to continuous consumption because everyday life every individual can be seen from their consumption activities. This makes researchers want to know the consumption of social media among students of SMP Negeri 2 Srengat, Blitar Regency. This researcher revealed the form of hyperreality and simulacra and the form of consumption of the application sign which is again a trend among young people today. The theory used in this study uses the theory of Hyperreality and Simulacra Jean Baudrillard. The method in this study uses a qualitative approach to the type of phenomenology. The data was obtained through a process of in-depth interviews and participatory observation to 4 students of SMPN 2 Srengat Blitar Regency who played Tik Tok which were selected by purposive sampling method. Researchers try to find out and explain the motive of using Tik Tok not as entertainment but as consumption of signs so that their social status is recognized as a contemporary child. The results showed that student hyperreality showed that students were chasing instant popularity like famous artists, that students wanted to be artists like those idolized in pseudo-reality. Students exaggerate the reality in Tik Tok's social media to show that they can become like the famous artists in Tik Tok